Pengaruh Komitmen Organisasi, Budaya Organisasi dan Motivasi terhadap Kinerja Karyawan PT. Hantar Hamparan Hasil di Pasuruan: The Influence of Organizational Commitment, Organizational Culture and Motivation on Employee Performance at PT. Send Overlay Results in Pasuruan - Rizal, As’at; Pebrianggara, Alshaf; Ansori, Achmad (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study was to determine the factors that influence the performance of employees at PT. Introduce Results Overlay which includes Organizational Commitment (X1) Organizational Culture (X2) and Work Motivation (X3). This study uses a quantitative method sample 60 employees at PT. Deliver Overlay Results as respondents. Data collection is done using questionnaires. The data were analyzed using statistical , namely by using multiple regression analysis, the processing of which was carried out with the SPSS version 25.0 program. 1) The results of the analysis prove that the Organizational Commitment, Organizational Culture and Motivation variables simultaneously affect the performance of employees at PT. Deliver Results Overlays. 2) The results of the analysis prove that Organizational Commitment and Motivation have a partial effect on Employee Performance, while Organizational Culture has no partial effect on Employee Performance. 3) Result prove that between Organizational Commitment, Organizational Culture and Motivation, Motivation variables have the most significant influence on Employee Performance at PT. Deliver Results Overlays.